Community Satisfaction for People with Physical Disabilities in Mubi: The Impact of Home Modification - Okoye, K. C. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study examined the relationship between home modification and community satisfaction for people with physical disability that effect mobility in Mubi, North Eastern Nigeria. A total of 50 people with physical disabilities that effect mobility, comprising of 25 adults in Mubi North and 25 adults in Mubi South local government areas of Adamawa state were randomly selected. Home modifications relating to; entrance to the buildings, access to goods and services, usability of rest rooms, were implemented for people in Mubi North, while people in Mubi South waited for their turn. Vreugdenhil & Rigby General Community Satisfaction Scale (GCSS) was used as the measurement tool and administered one on one to the respondents before the execution of home modifications and after three months of the modifications. Responses to each item in the GCSS are provided on a 5 point Likert scale ranging from “strongly disagree” to “strongly agree”. Findings from the study indicates that community satisfaction was significantly enhanced for the participants in Mubi North after home modification with mean score 4.111 (p=0.001), as compared to the waiting participants in Mubi south with score1.780 (P=0.126). Overall Satisfaction with modification outcomes has a significant positive correlations at p<0.01 level with the variables of home modification. The study recommends that home modification should be recognized as a key element for residential satisfaction that enhances safety, accessibility, and comfort, allowing individuals, especially those with disabilities, to live independently and satisfied within their own homes and communities.